2019
DOI: 10.18510/hssr.2019.7242
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Student Teachers’ Perception of Using Google Classroom in a Blended Course

Abstract: Purpose of the study: The strategic and learning media course in the Informatics Engineering Education department for pre-service student teachers apply a blended learning method. The purpose of this method is to integrate between face-to-face meetings in the classroom and distance learning by using internet-based Learning Management System (LMS) media. This study aims to determine the perceptions of the informatics’ pre-service student teacher, which utilize the Google Classroom LMS. Methodology: The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…However, the problems students faced using GC are similar to those associated with other learning management systems such as internet speed and coverage, difficulty understanding platform operation, the need to spend more time practicing and studying, and under-utilization [ 12 , 15 ]. To build, implement, and motivate students to use the new learning platform, we adopted the technology acceptance model (TAM) as the research framework to design educational materials and assess students’ acceptance and use of GC [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the problems students faced using GC are similar to those associated with other learning management systems such as internet speed and coverage, difficulty understanding platform operation, the need to spend more time practicing and studying, and under-utilization [ 12 , 15 ]. To build, implement, and motivate students to use the new learning platform, we adopted the technology acceptance model (TAM) as the research framework to design educational materials and assess students’ acceptance and use of GC [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies related LMS in teaching and learning; for examples, its considerations [12][13][14], implementation [15][16][17], and evaluations [18][19][20] Those previous researches are quite similar to this research, which discuss the implementation of an LMS platform in teaching and learning. However, the barriers to using LMS on speaking tasks have not been studied yet, as we know.…”
Section: Introductionmentioning
confidence: 58%
“…Another opinion revealed that microteaching is a technique that is used to train student teachers in a minimized and restricted or artificial teaching environment. Microteaching simulations are carried out in classrooms with students formed in groups [12]. Another understanding states that microteaching is a pre-service teacher's teaching practice for a reduced time and class size in front of his / her peers and the mentors, tutors or, professors under their supervision.…”
Section: Microteachingmentioning
confidence: 99%